2014
DOI: 10.1016/j.pedneo.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B Virus-associated Pneumonia in Pediatric Patients: Clinical Features, Laboratory Data, and Chest X-ray Findings

Abstract: Pneumonia should be considered in pediatric patients with influenza B virus infection presenting with younger age, higher white blood cell count, lower hemoglobin, and higher C-reactive protein level. The CXR findings were varied. Patients with pleural effusion and positive bacterial culture may have more severity of clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…6 Similar results were observed in a study from Taiwan were the incidence of IBV associated pneumonia was 18.4%. 7 The median age of IBV infection in our study was 5.85 years which is consistent with other studies across the globe where the reported incidence is highest among pre school and school going children. 9 Apart from respiratory symptoms, IBV is also known to cause gastro intestinal symptoms,7 encephalitis,10 seizures,10 myocarditis,11 musculoskeletal involvement including arthritis and myalgia.12 In our study we observed that 10/11 (90%) children with pneumonia had vomiting.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…6 Similar results were observed in a study from Taiwan were the incidence of IBV associated pneumonia was 18.4%. 7 The median age of IBV infection in our study was 5.85 years which is consistent with other studies across the globe where the reported incidence is highest among pre school and school going children. 9 Apart from respiratory symptoms, IBV is also known to cause gastro intestinal symptoms,7 encephalitis,10 seizures,10 myocarditis,11 musculoskeletal involvement including arthritis and myalgia.12 In our study we observed that 10/11 (90%) children with pneumonia had vomiting.…”
Section: Discussionsupporting
confidence: 92%
“…Oseltamivir therapy is recommended within 48 hours of the onset of fl ulike symptoms in children at high risk of developing complications due to infl uenza viral infections and empirical anti viral prophylaxis should be administered to close contacts. 7 None of our children in the high risk category were vaccinated against infl uenza indicating low awareness among the general population and low coverage of the vaccine. Our study was limited due to the small sample size and we focussed mainly on viral aetiology since it is understudied in our region.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…There is some overlap in the imaging presentation of COVID-19 and other entities, including infections (Influenza A, Influenza B, or Mycoplasma Pneumonia), inflammatory processes (e-cigarette vaping associated lung injury (EVALI) or hypersensitivity pneumonitis (HP)), and eosinophilic lung disease in the pediatric population, and therefore a low COVID-19 prevalence could lead to false positive results. 13,14,[18][19][20][21][22][23][24] Second, introducing the term COVID-19 pneumonia into the patient's clinical record may cause ordering physicians to feel constrained in future clinical decision making. Open and careful discussion with the referring doctor concerning the level of clinical suspicion for COVID-19 should help mitigate these issues.…”
Section: N P R E S S Considerations For Standardized Reporting Of Imentioning
confidence: 99%